프랜차이즈에서 리더십스타일의 선행요인과 성과요인에 관한 연구 - 이의준; 김상덕; Lee, Eui-Joon; Kim, Sang-Deok (Journal of distribution science, 2011)
The relationship between buyers and sellers is changing into a long-term relationship. A number of distribution channel researchers have determined that the behavior of distribution channel members can be characterized by relational exchanges. The members of relational distribution channels may be perceived as strategic partners; however, even within these arrangements, member asymmetries may exist, which can create unequal distributions of power and dependence. Thus, as all distribution channel members may not be equal in power, it is possible that a less-dependent channel leader may emerge. Therefore, leadership in distribution channels is a very important variable. Distribution channel leadership can be defined as the activities undertaken by the distribution channel leader to influence the marketing programs and strategies of channel members. A distribution channel's performance is influenced by the leadership style of the channel leader. Although research on channel leadership styles can be broadly categorized, many researchers have dealt with analyzing distribution channel leadership by using the power-influence approach, which includes looking at variables, such as power, power base, and influence strategies. Moreover, they have examined the direct relationship between leadership styles and performance. Many distribution channel scholars have attempted to justify the application of leadership styles identified in alternative leadership theories to the inter-organizational context of distribution channels. They have made suggestions regarding how great the usefulness of leadership style as a strategy is to secure the compliance of distribution channel members and have conceptually and empirically linked it to channel-related phenomena, such as manifest conflict, cooperation, channel efficiency, and effectiveness. However, as few empirical studies have examined the antecedents and consequences of leadership styles, research on leadership style can be considered nascent. Thus, it is required to investigate the antecedents and consequences of the leadership style of a distribution channel leader. This study aims to empirically identify whether there are influences of the antecedents of leadership on two different leadership styles, and to reveal whether these leadership styles induce any consequences. The research subjects were 220 franchisees. Research findings are as follows: First, the results show a positive effect of technological capability on transformational relationships. However, it does not have a significant effect on transactional leadership. Second, innovation-oriented organizational culture has negatively influenced both leaderships. However, task-oriented organizational culture positively and significantly influenced both forms of leadership. Third, the ethics of leaders has influenced both leadership styles positively and significantly. Fourth, regarding consequences, transformational leadership strengthens financial performances, whereas it weakens relational citizenship behaviors. However, transactional leadership positively influences relational citizenship behavior whilst negatively affecting financial performance. 본 연구는 1980년대 이후 관심을 끌고 있는 리더십연구를 프랜차이즈시스템의 본부와 가맹점관계에 적용하였다. 연구의 목적은 여러 선행연구 및 자료에서 나타난 핵심이슈들 즉, 윤리성, 정보기술, 그리고 조직문화를 리더십의 선행요인으로 보고 이들과 리더십스타일 및 성과 간 관계를 규명하고자 한다. 이를 위하여 프랜차이즈의 3개 업종, 즉 외식업, 서비스업, 도소매업의 가맹점 220업소의 점주를 대상으로 자료를 수집 분석한 결과 거래적 조직문화가 리더십을 강화시키고, 기술역량은 변혁적 리더십만을, 윤리성은 경로리더십유형에 관계없이 모두 영향을 미쳤다. 리더십의 성과에는 변혁적 리더십은 재무적 성과를 강화시키나 거래적 리더십은 관계시민행동을 강화시키는 것으로 나타났다. 이는 프랜차이즈본부가 거래관계를 중시한 과업지향적 문화를 조성하여 리더십을 강화하고 윤리성의 확립과 기술역량을 축적해야 하며 변혁적 리더십과 거래적 리더십을 선택적으로 발휘하여 재무적 성과와 관계시민행동을 촉진해야함을 나타내 보였다. 본 연구는 "리더십조건은 만들어 질수 있다"는 메시지의 전달과 정부의 유통정책에 경로리더의 양성과 활용기반을 마련하며 윤리교육과 윤리가이드라인이 필요함에 대한 단서를 제공하였다.